Adherence to Medical Treatment in Elderly Patients with Coronary Artery Disease in the Settings of Primary Outpatient Care - S. K. Zyryanov; S. B. Fitilev; A. V. Vozzhaev; I. I. Shkrebneva; N. N. Shindryaeva; D. A. Klyuev; L. N. Stepanyan; A. M. Lutsenko; A. T. Tsai; A. A. Danilova (Рациональная фармакотерапия в кардиологии, 2021)
Aim. To study medication adherence in elderly patients with coronary artery disease (CAD) in primary care practice.Material and methods. The study conducted in out-patient clinic of Moscow city. 293 elderly (≥65 years) patients with established CAD included. The following patient data obtained via electronic medical record system: demography, medical history, modifiable risk factors and prescribed pharmacotherapy. Level of medication adherence measured by Morisky scale (MMAS-8) via telephone survey.Results. According to Morisky scale high adherence was identified in 146 (49.8%) elderly patients, moderate adherence – in 99 (33.8%) patients, low adherence – in 48 (16.4%) patients. Analysis of specific questions of the scale done in non-adherent patients revealed signs of unintentional non-adherence due to forgetfulness (45.9%) and signs of intentional non-adherence due to patients feeling worse (35.8%) or better (28.4%). By means of dichotomic interpretation of Morisky scale results the population under research was divided into two groups: 147 (50.2%) non-adherent patients and 146 (49.8%) – totally adherent patients. These groups were comparable in terms of sex (female 71.2 vs 68.0%; p>0.05) and age (median 73.5 vs 73.0 years; p>0.05) distribution, and medical history: myocardial infarction (39.0% vs 38.8%), atrial fibrillation (37.0 and 41.5%), chronic heart failure (90.4% vs 91.2%), diabetes (26.7% vs 24.5%). There were fewer smokers in adherent group (0.7% vs 6.5%; p<0.05). As primary antianginal pharmacotherapy adherent and non-adherent patients were equally prescribed beta-blockers (75.3% vs 75.5%; p>0.05). Drugs that improve prognosis were also prescribed comparably: antiplatelets (66.4% vs 61.9%; p>0.05), anticoagulants (36.3% vs 44.9%; p>0.05), statins (82.2% vs 79.6%; p>0.05), renin-angiotensin system inhibitors (89.0 and 87.8%; p>0.05). Adherent patients had lower mean values of lipids: total cholesterol (4.7±1.2 vs 5.2±1.4 mmol/l; p<0.05) and low density cholesterol (2.4±0.9 vs 2.8±1.2 mmol/l; p<0.05). Non-adherent elderly patients made more visits to general practitioner (median 5 vs 3 visits; p<0.05). Share of patients receiving drugs within supplementary pharmaceutical provision program was comparable in both groups (53.7% vs 50.7%; p>0.05).Conclusion. Half of elderly patients with CAD are non-adherent to treatment in primary care setting. Medical history and structure of pharmacotherapy do not influence level of adherence in this population. Among adherent patients fewer individuals smoke and mean values of lipids are lower. Non-adherent elderly patients cause higher load on general practitioner, supplementary pharmaceutical provision program provided no better adherence in the population under research.